(untitled) (Journal of Applied Learning and Teaching, 2020)
Increasingly, management students are required to demonstrate their critical thinking and problem-solving skills upon entering the workforce. This prompts educators to ask how can students be taught to think critically and what kind of exercises can be built into undergraduate learning to ensure critical thinking and problem-solving are practiced? As such, peer assessment as learning promotes active critical thinking and problem-solving via collaborative assessment and exchange of feedback amongst peers. This classroom exercise is designed for students on any management undergraduate course to develop their critical thinking and problem-solving skills through a peer assessment and feedback task. Adopting Edward de Bono’s approach to thinking encourages students to think in a focused, deep and critical way about the piece of work they are assessing. Through this exercise they obtain the benefits of developing critical thinking skills and further learn to develop a collaborative approach to problemsolving in the provision of feedback and feedforward.